Synthesis of triphenylene-based triptycenes via Suzuki-Miyaura cross-coupling and subsequent Scholl reaction - Reinhard, Dennis; Rominger, Frank; Mastalerz, Michael (The journal of organic chemistry, 2015)
A two-step method (Suzuki-Miyaura cross-coupling, followed by Scholl oxidation) to triphenylene-based triptycenes is described, rendering a variety of π-extended triptycenes accessible in high yields and without the necessity of column chromatography purification. The versatility of this reaction has been demonstrated in the synthesis of a supertriptycene in only four steps and high yields.
Gesehen am 17.06.2020